A) D(0,-1) B) C(-1,0) C) E(0,0) D) A(0,1)
A) EA=1/2 B) EF=1 C) EG=1 D) FG=1
A) x2-y2=1 B) x+y2=1 C) x2+y=1 D) x2+y2=1
A) 4 cm B) 2 cm C) 1 cm D) 3 cm
A) 1 cm B) 4 cm C) 3 cm D) 2 cm
A) (x+1)2+(y+1)2=(3)2 B) (x+1)2+(y-1)2=(3)2 C) (x+1)2+(y-1)2=(2)3 D) (x-1)2+(y-1)2=(3)2
A) x2-y2=1 B) x2.y2=1 C) x2+y2=-1 D) x2+y2=1
A) Reemplazar el valor de "x" en la ecuación x2+y=1 y despejar "y". B) Reemplazar el valor de "x" en la ecuación x2+y2=1. C) Reemplazar el valor de "x" y despejar "y". D) Reemplazar el valor de "x" en la ecuación x2+y2=1 y despejar "y".
A) sen30°=1/2 B) tan30°=1 C) cot30°=1 D) cos30°=1/2
A) tanα=co/ca B) senα=co/h C) cotα=1/co D) cosα=ca/h |